2017
DOI: 10.1016/j.pmedr.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Memorizing fruit: The effect of a fruit memory-game on children's fruit intake

Abstract: Food cues of palatable food are omnipresent, thereby simulating the intake of unhealthy snack food among children. As a consequence, this might lead to a higher intake of energy-dense snacks and less fruit and vegetables, a habit that increases the risk of developing chronic diseases. The aim of this experimental study is to examine whether playing a memory game with fruit affects fruit intake among young children. We used a randomized between-subject design with 127 children (age: 7–12 y) who played a memory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
1
14
0
3
Order By: Relevance
“…One of the strengths of the current study is that we examined the in uence of a popular real t in uencer on the food consumption behavior of young people. Food marketing research has predominantly focused on the in uence of food advertising of unhealthy foods on eating behavior among children and adolescents (Boyland et al 2016;Folkvord and Van 't Riet, 2018;Folkvord et al 2016), while research examining the effects of food marketing for healthy foods is scarce Folkvord et al 2017Folkvord et al , 2018Folkvord et al , 2019a. Considering that a great number of people do not consume enough fruit and vegetables (Miller et al 2019), it is of great importance to examine the potential of food promotion techniques of healthier foods.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strengths of the current study is that we examined the in uence of a popular real t in uencer on the food consumption behavior of young people. Food marketing research has predominantly focused on the in uence of food advertising of unhealthy foods on eating behavior among children and adolescents (Boyland et al 2016;Folkvord and Van 't Riet, 2018;Folkvord et al 2016), while research examining the effects of food marketing for healthy foods is scarce Folkvord et al 2017Folkvord et al , 2018Folkvord et al , 2019a. Considering that a great number of people do not consume enough fruit and vegetables (Miller et al 2019), it is of great importance to examine the potential of food promotion techniques of healthier foods.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find previous studies of branded high nutritional value foods placed in video format, as this type of food is usually presented as non-branded. Findings about non-branded high nutritional value food placements are not conclusive: although some studies found effects on children's choices [24] and intake [20], most of the previous literature did not [8,21,23]. In a recent study by Binder, Naderer, and Matthes (2019) [38], it was found that a non-branded high nutritional value food (raspberries) did not trigger effects on behavioral responses in children aged 6-10 years.…”
Section: Type Of Food and Modalitymentioning
confidence: 95%
“…Additionally, although the studies that analyze the effects of food placements are mostly about branded foods, several studies about non-branded food placements can also be found. To our knowledge, approximately half of the studies about the effectiveness of non-branded food placements have focused on foods placed in videogames [18][19][20][21], whereas the other half have focused on video format, such as cartoons or TV shows [8,[22][23][24]. Regarding the studies that analyze non-branded foods placed in cartoons, we only found one study that investigated the influence of type of food on children's behavior [8].…”
mentioning
confidence: 99%
“…Individual susceptibility to advertising messages effects may in particular be considered when it comes to influencer marketing by social influencers, as these social influencers specifically design their messages for existing community of engaged and young followers, thereby reducing their persuasion knowledge activation and increasing the parasocial interaction, leading to a more positive attitude towards the advertised product and increasing purchase intentions [40][41][42]. In addition, promotion activities by peer-aged influencers are perceived as more credible and authentic because adolescents believe they will receive an honest advice or opinions about certain brands or products.…”
Section: Promoting Healthy Foods On Social Mediamentioning
confidence: 99%